Pseudo-V2 control with adaptive compensation for fast-transient current-mode buck converter. Issue 9 (September 2015) - Zeng, Yanhan; Tang, Weijie; Li, Yuao; Tan, Hong-Zhou
Abstract A type of pseudo-V2 control, with on-chip adaptive compensation to achieve fast transient (FT) response for current mode DC–DC buck converter, has been proposed and simulated using 0.18 μm CMOS technology in this paper. Based on a new on-chip capacitor multiplier, adaptive compensation is achieved by making the compensation capacitance to track the load current. The proposed pseudo-V2 control utilizes the output ripple to determine the duty cycle during load transient. Thus the overshoot/undershoot voltage and the transient recovery time are effectively reduced. Simulation results demonstrate the transient ripple is smaller than 50 mV and the transient recovery time is shorter than 10 μs for a 450 mA load current step. The maximum power conversion efficiency is 94.6% at 1 MHz switching frequency when input and output voltages are 5 V and 1.8 V, respectively.